Operational Risk Escalation: An Empirical Analysis of Financial Services - Zubiy, Irina (2014)
The aim of this research study is to investigate operational risk reporting behavior and policy dissemination in the financial services in 2 different countries (Russia and United Kingdom). It examines the measurement of 'people risk' and the collection of valid operational risk data comparing the results between British and Russian employees and the combined sample. Two articles of Bryce et al ('Operational risk escalation: an empirical analysis of UK call centres' and 'Strategic lessons from banking compliance? The importance of risk escalation for Solvency II implementation') formed the basis for my future dissertation topic. A questionnaire survey was administered to 302 employees (33% British and 67% Russians). The analysis of the predisposition of financial services’ employees to escalate operational risks within their working environment is measured using the Theory of Planned Behavior (Ajzen, 1991). Data collected were analyzed using multivariate regression. The Theory of Planned Behavior model of combined sample explained 22,8 percent of the variability in intention, providing support for its predictive power. The empirical analysis indicates the effects of 'Attitude' and 'Perceived Behavioral Control' that significantly affect employee's intention to escalate operational risk losses/events. The results confirmed that financial institutions staff intentions towards the escalation of risk events rely upon the perceived difficulty level of performing the behavior and reflect employees’ past experience as well as anticipated barriers – attitude. Perception of social norms however did not statistically significant affect the employees’ intention. Future investigations should be done in banking sector in order to fully evaluate the significance of theory of planned behavior. The findings of this study will have implications for financial services to better understand their employees’ behavioral intention towards escalating risk events and therefore integrate adequate norms into risk management process as prescribed appropriate behavior.